Discrimination of prostate cancer from benign disease by selective measurements of serum subfractions of free PSA that are not internally cleaved at Lys145-Lys146 - Nurmikko, P; Steuber, T; Haese, A; Pettersson, K; Hammerer, P; Huland, H; Lilja, H (2002)
Background: The free PSA fraction in serum of patients with various prostatic disorders is essentially unreactive with the anti-proteases in blood. Recently reported data show that it is likely to consist of a mixture of proPSA, internally cleaved PSA forms, and possibly other uncharacterized forms. Currently there are no specific methods available to measure the different free PSA subfractions and to evaluate their diagnostic or prognostic value. Methods: A novel immunoassay has been developed that measures intact, free PSA, which is not internally cleaved at Lys145-Lys146. Sera with total PSA-levels (PSA-T) from 2 to 8 ng/mL were obtained from 112 men without prostate cancer (with negative sextant biopsy or benign prostatic hyperplasia [BPH]) and 125 men with biopsy-proven clinically localized prostate cancer (PCa) before treatment. The aim was to determine levels of intact free PSA (fPSA-I) in serum of these patients and to determine the diagnostic value of fPSA-I. Results: The ratio of intact fPSA to free PSA (PSA-F) is significantly higher in serum from men with prostate cancer (median 47.6%) compared to those without cancer (median 41.3%; P = 0.0057). Logistic regression analysis was used to calculate the predictive values for fPSA-I + PSA-F + PSA-T (Log II, F, TI). Analysis showed that each of the three analytes contributed significantly to the discrimination of PCa from non-cancer sera. The area under the curve (AUC) of Log [I, F, T] was significantly larger (AUC = 0.7041) compared to the AUC of PSA-T (AUC = 0.5960; P = 0.0038) whereas the AUC of F/T ratio (AUC = 0.6669) was not (P= 0.16). Conclusion: The ratio of intact to free PSA was significantly higher in prostate cancer compared to the noncancer or benign group. Combination of fPSA-I, PSA-F and PSA-T improved discrimination of prostate cancer from non-cancer sera, especially at low PSA-T concentrations.